PERUBAHAN GANGGUAN DAYA INGAT DENGAN PEMBERIAN TERAPI SENAM OTAK PADA LANSIA DI DESA SUKORENO KECAMATAN KALISAT - Eka Fitriya Ladjiru; Sri Ummi; Wahyuni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Memory is a person's ability to recall information that has been learned and stored in the brain. Measures to prevent / reduce memory impairment is to provide Brain Exercise Therapy. The brain exercise movement itself is a movement to stimulate the right and left brain, stimulating the system associated with feelings / emotional. Other benefits of brain gym (brain gym) are to improve language skills, creativity, and the elderly feel healthier and improve memory. The purpose of this study was to determine changes in memory and identify memory disorders in the elderly after being given brain exercise therapy in Soekarno Village, Jember Regency. This study used a pre-experimental one group pre-test post-test design. The population is 45 respondents and the sample is 40 respondents. The sample technique used is simple random sampling. The results of the study before given brain exercise therapy, amounting to 23% experienced severe memory impairment, 30% moderate memory impairment, 47% mild memory impairment, 0% no memory impairment. After treatment, 2% experienced severe memory impairment, 18% moderate memory impairment, 57% mild memory impairment, 8% no memory disturbance. Results of data analysis using Wilcoxon signed rank test with alpha (a) of 0.05 obtained, 0,000 <a 0.05, which means there is a change in memory disorders in the elderly after being given brain exercise therapy. This therapy is very easy to do so the individual is expected to be applied by the elderly according to the correct procedure